Transalkylation catalyst, method of making and using and method of transalkylating aromatic hydrocarbons in liquid phase
Patent Information
- Application Number
- CN202310867284.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-07-14
AI Technical Summary
[0009]本发明的目的是为了克服现有技术存在的芳烃液相烷基转移反应中,芳烃转化率低、二甲苯选择性低的问题,提供一种烷基转移催化剂、制备方法及其应用和芳烃液相烷基转移的方法,该催化剂有利于促进芳烃液相烷基转移反应进行,具有芳烃转化率高、二甲苯选择性高的特点
[0018]本发明提供的烷基转移催化剂采用Beta/ZSM-12共生分子筛和二氧化钛配合,有利于促进含有甲苯和C9+芳烃物料进行烷基转移反应。在液相反应条件下,该催化剂也具有较高的芳烃转化率和二甲苯选择性,催化剂的制备方法简单,可用于对二甲苯的工业生产中。
Smart Images

Figure BDA0004339796300000101 
Figure BDA0004339796300000102 
Figure BDA0004339796300000151
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalysts, specifically to an alkyl transfer catalyst, its preparation method, its application, and a method for liquid-phase alkyl transfer of aromatics. Background Technology
[0002] Xylene, as an important organic chemical raw material, has a wide range of industrial applications. It can be used as a solvent in industries such as coatings, resins, dyes, and inks; as a synthetic monomer or solvent in industries such as pharmaceuticals, explosives, and pesticides; and as a component of high-octane gasoline. The most widely used xylene product is para-xylene, which is used to produce polyesters, and its demand is increasing daily. The main industrial methods for producing xylene include: 1) using naphtha as raw material through a series of processes such as catalytic reforming, separation, and purification to obtain xylene and other high-value-added products; 2) utilizing toluene disproportionation and alkyl transfer processes, i.e., the conversion of toluene and C9 aromatics into benzene and xylene under the action of a catalyst. This reaction mainly includes: toluene disproportionation reaction and alkyl transfer reaction. Toluene disproportionation reaction generally refers to the reaction of two toluene molecules to produce one benzene molecule and one xylene molecule. Alkyl transfer reaction generally refers to the reaction of one toluene molecule and one trimethylbenzene molecule under the action of a catalyst to produce two xylene molecules.
[0003] Conventional toluene disproportionation and alkyl transfer processes are typically carried out at relatively high reaction temperatures (350-410℃). Materials are mixed in the gas phase and contact the catalyst for conversion. The reaction usually consumes a large amount of hydrogen. The target products, benzene and xylene, are separated from the reactants. Unreacted useful materials are separated and recycled. Excessive cracking during the reaction often results in the loss of aromatics, and a small amount of heavy aromatic byproducts are also generated. These byproducts cannot be converted and must be discharged, all of which increase energy consumption and production costs. Currently, higher demands are being placed on refining and chemical enterprises regarding energy conservation, emission reduction, quality improvement, and efficiency enhancement.
[0004] Although major international oil companies have developed new disproportionation and alkyl transfer catalysts in recent years, the energy consumption of these units remains high. Therefore, the development of liquid-phase aromatic alkyl transfer catalysts and related technologies is proposed to alleviate the high energy consumption problem in xylene production by refineries. Liquid-phase aromatic alkyl transfer technology involves mixing reactants in a liquid phase and contacting them with a catalyst for conversion. The reaction temperature is typically between 200-330℃. It offers advantages such as low energy consumption, low aromatic loss, few byproducts, and high xylene selectivity. While hydrogen is required in the reaction, the amount used is much lower than in gas-phase reactions; hydrogen simply needs to be dissolved in the reactants.
[0005] CN108779047A discloses a method for liquid-phase aromatic alkyl transfer. The catalyst used in this invention includes a molecular sieve with a three-dimensional 12-membered ring framework structure and a molecular sieve with a one-dimensional 12-membered ring framework structure, with at least [number missing] pore channels. The method comprises acidic microporous materials and / or molecular sieves having an MWW framework structure. The method includes alkyl transfer, wherein at least a portion of the feed to the alkyl transfer method is in the liquid phase; some embodiments include a liquid-phase alkyl transfer method for naphthalene-containing feed streams.
[0006] CN109790084A discloses a method for alkyl transfer of heavy aromatics, a method for producing xylene from C9+ aromatics, comprising contacting a first feedstock containing C9+ aromatics with a catalyst under effective vapor-phase dealkylation conditions in the presence of 0 wt% or more hydrogen, to dealkylate a portion of the C9+ aromatics and produce a first product containing benzene, toluene, and residual C9+ aromatics. A second feedstock containing C9+ aromatics and benzene and / or toluene is contacted with a second catalyst under effective liquid-phase C9+ alkyl transfer conditions to alkylate at least a portion of the C9+ aromatics and produce a second product containing xylene.
[0007] CN109803944A discloses a method for disproportionation and alkyl transfer of heavy aromatic hydrocarbons. It includes: (a) contacting a toluene-containing feedstock with a first catalyst under effective gas-phase toluene disproportionation conditions to disproportionate the toluene and produce a first product comprising benzene, unreacted toluene, and a greater amount of p-xylene than the equilibrium amount; and (b) contacting a feedstock comprising C9+ aromatic hydrocarbons and benzene with a second catalyst under effective C9+ alkyl transfer conditions, in the presence of 0 wt% or more hydrogen having a hydrogen / hydrocarbon molar ratio of 0-10, to perform alkyl transfer of the C9+ aromatic hydrocarbons and produce a second product comprising xylene.
[0008] Current technologies suffer from problems such as low aromatic conversion efficiency and low xylene selectivity under liquid phase conditions. Summary of the Invention
[0009] The purpose of this invention is to overcome the problems of low aromatic conversion rate and low xylene selectivity in the existing technology of aromatic liquid-phase alkyl transfer reaction, and to provide an alkyl transfer catalyst, preparation method and application thereof, and method for aromatic liquid-phase alkyl transfer. This catalyst is beneficial to promoting the aromatic liquid-phase alkyl transfer reaction and has the characteristics of high aromatic conversion rate and high xylene selectivity.
[0010] To achieve the above objectives, a first aspect of the present invention provides an alkyl transfer catalyst, wherein the catalyst comprises a Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and a binder.
[0011] Preferably, based on the total amount of catalyst, the weight percentage of the Beta / ZSM-12 symbiotic molecular sieve is 67-88%, more preferably 74-85%; the weight percentage of titanium dioxide is 2-8%, more preferably 3-6%; and the weight percentage of the binder is 10-25%, more preferably 10-20%.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned alkyl transfer catalyst, the method comprising the following steps:
[0013] (1) In the presence of a solvent, the Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, binder and optional extrusion aid and adhesive solvent are mixed;
[0014] (2) The mixture obtained in step (1) is shaped, and then dried and roasted.
[0015] The third aspect of this invention provides the application of the alkyl transfer catalyst described in the first aspect in the liquid-phase alkyl transfer reaction of aromatics.
[0016] A fourth aspect of the present invention provides a method for liquid-phase alkyl transfer of aromatics, the method comprising: contacting a mixture containing toluene and C9+ aromatics with a catalyst under liquid-phase reaction conditions in the presence of hydrogen, wherein the catalyst is selected from the alkyl transfer catalyst described in the first aspect.
[0017] The beneficial effects obtained by the present invention through the above technical solution are as follows:
[0018] The alkyl transfer catalyst provided by this invention employs a combination of Beta / ZSM-12 symbiotic molecular sieve and titanium dioxide, which is beneficial for promoting alkyl transfer reactions of materials containing toluene and C9+ aromatics. Under liquid-phase reaction conditions, this catalyst also exhibits high aromatic conversion and xylene selectivity. The catalyst preparation method is simple and can be used in the industrial production of p-xylene. Detailed Implementation
[0019] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0020] The first aspect of the present invention provides an alkyl transfer catalyst, wherein the catalyst comprises a Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and a binder.
[0021] In this invention, titanium dioxide is added in combination with Beta / ZSM-12 symbiotic molecular sieve. Titanium dioxide adjusts the acidity of the symbiotic molecular sieve, improves the stability of the alkyl transfer catalyst, and inhibits the occurrence of side reactions.
[0022] In this invention, the symbiotic molecular sieve refers to a molecular sieve material containing two or more crystal structures that is directly synthesized during the synthesis process.
[0023] In this invention, a Beta / ZSM-12 symbiotic molecular sieve is used. The material contains two different molecular sieve structures: a three-dimensional twelve-membered ring Beta molecular sieve and a one-dimensional twelve-membered ring ZSM-12 molecular sieve. Compared with a simple mechanical mixture of Beta molecular sieve and ZSM-12 molecular sieve, the symbiotic molecular sieve has an interconnected composite pore structure, which makes it easier for reactants to access the active sites. The complementary acidity distribution can synergistically catalyze and improve the activity of alkyl transfer reactions under liquid phase conditions.
[0024] According to the present invention, preferably, based on the total amount of catalyst, the weight percentage of the Beta / ZSM-12 symbiotic molecular sieve is 67-88%, more preferably 74-85%; the weight percentage of the titanium dioxide is 2-8%, more preferably 3-6%; and the weight percentage of the binder is 10-25%, more preferably 10-20%.
[0025] In this invention, the contents of Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and binder in the catalyst are calculated by the amount of feed.
[0026] According to the present invention, preferably, the SiO2 / Al2O3 molar ratio of the Beta / ZSM-12 symbiotic molecular sieve is 10-40, for example 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, 40, or any range between the two, preferably 10-20.
[0027] In this invention, the Beta / ZSM-12 symbiotic molecular sieve with a lower SiO2 / Al2O3 molar ratio is used. Its molecular sieve acid content is greater, which helps to increase the active sites in the molecular sieve. Under the low-temperature reaction conditions in the liquid phase, the alkyl transfer catalyst can also have high activity, high aromatic conversion rate, and high xylene selectivity.
[0028] In this invention, the silicon-aluminum molar ratio SiO2 / Al2O3 of the Beta / ZSM-12 symbiotic molecular sieve was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). The testing instrument was a Varian 725-ES series ICP-AES instrument.
[0029] According to the present invention, preferably, the average grain size of the Beta / ZSM-12 symbiotic molecular sieve is less than 500 nm, more preferably 100-300 nm. The average grain size of the Beta / ZSM-12 symbiotic molecular sieve was observed using a Philips XL30E scanning electron microscope. In the present invention, the Beta / ZSM-12 symbiotic molecular sieve has a small average grain size, a large specific surface area, and numerous and easily accessible active sites, resulting in a catalyst with high catalytic activity.
[0030] The binder described in this invention has a wide range of choices and can be any conventional binder in the art, enabling better bonding between the Beta / ZSM-12 symbiotic molecular sieve and titanium dioxide, thereby improving the catalytic activity of the prepared catalyst. According to this invention, preferably, the binder is silicon dioxide and / or aluminum oxide.
[0031] According to the present invention, preferably, the coexistence ratio of Beta molecular sieve and ZSM-12 molecular sieve in the Beta / ZSM-12 symbiotic molecular sieve is 0.25-4:1, for example, 0.25:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, or a range between the two, preferably 0.5-2:1. Using a specific coexistence ratio of Beta / ZSM-12 symbiotic molecular sieve not only facilitates the diffusion of hydrocarbon molecules but also improves the conversion rate of aromatics during alkyl transfer reactions under liquid-phase reaction conditions, and is more conducive to improving xylene selectivity.
[0032] In this invention, the co-occurrence ratio is the weight ratio of Beta molecular sieve to ZSM-12 molecular sieve in the Beta / ZSM-12 co-occurring molecular sieve. The co-occurrence ratio is obtained by calculating the ratio of the characteristic peak areas of the two crystalline phases in the XRD pattern.
[0033] In this invention, the source of the Beta / ZSM-12 symbiotic molecular sieve is not particularly limited; it can be commercially available or prepared using existing methods. Using a Beta / ZSM-12 symbiotic molecular sieve that meets the above parameter requirements, in combination with titanium dioxide, can effectively improve the catalytic activity of the catalyst.
[0034] According to a specific embodiment of the present invention, the Beta / ZSM-12 symbiotic molecular sieve is prepared by the following method:
[0035] (A) Inorganic base, quaternary ammonium salt, silicon source, aluminum source and deionized water are mixed. The reaction mixture has the following molar ratio: SiO2 / Al2O3 = 15-50:1, quaternary ammonium salt TEA + / SiO2=0.1-0.5:1, inorganic base OH - / SiO2 = 0.2-0.5:1, H2O / SiO2 = 15-100:1, stir at 25-90℃, and age.
[0036] (B) After crystallization treatment, the product was cooled and taken out. After filtration, exchange, water washing, drying and calcination, Beta / ZSM-12 symbiotic molecular sieve was obtained.
[0037] In this invention, the crystallization conditions include: a crystallization temperature of 120-200℃ and a crystallization time of 48-96 hours. The crystallization reaction is carried out in a closed container under autogenous pressure.
[0038] In this invention, the calcination conditions for the symbiotic molecular sieve are calcination at 450-650℃ for 3-24 hours in an air atmosphere.
[0039] In this invention, the filtration, exchange, washing, and drying are conventional operations in the field, and those skilled in the art can make adaptive adjustments, which will not be elaborated here.
[0040] In this invention, the inorganic base, quaternary ammonium salt, silicon source, and aluminum source are conventional inorganic bases, quaternary ammonium salts, silicon sources, and aluminum sources in the art, and the Beta / ZSM-12 symbiotic molecular sieve required for the above-mentioned alkyl transfer catalyst can be obtained.
[0041] In this invention, preferably, the inorganic base is potassium hydroxide and / or sodium hydroxide. Preferably, the silicon source is selected from at least one of water glass, silica sol, silica gel, and tetraethyl orthosilicate. Preferably, the quaternary ammonium salt TEA... + The aluminum source is selected from at least one of tetraethylammonium bromide, tetraethylammonium chloride, and tetraethylammonium hydroxide. Preferably, the aluminum source is selected from at least one of boehmite, sodium aluminate, aluminum sulfate, and aluminum nitrate.
[0042] A second aspect of the present invention provides a method for preparing the alkyl transfer catalyst described in the first aspect, the method comprising the following steps:
[0043] (1) In the presence of a solvent, the Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, binder and optional extrusion aid and adhesive solvent are mixed;
[0044] (2) The mixture obtained in step (1) is shaped, and then dried and roasted.
[0045] In this invention, the amount of Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and binder added is based on obtaining the content of Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and binder in the catalyst described in the first aspect.
[0046] In this invention, unless otherwise specified, "optional" means containing or not containing, adding or not adding, using or not using. Specifically, step (1) of this invention may include an extrusion aid and / or a solvent, or may not include an extrusion aid and a solvent.
[0047] The types of extrusion aids described in this invention are well known to those skilled in the art. According to this invention, preferably, the extrusion aid is selected from at least one of guar gum powder, methylcellulose, hydroxypropyl methylcellulose, and dextrin.
[0048] In this invention, the amount of the extrusion aid is not particularly limited, and those skilled in the art can make adaptive adjustments as needed to ensure smooth subsequent molding. Preferably, the amount of the extrusion aid is 1-5% of the total weight of Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and binder on a dry basis, more preferably 1-3%.
[0049] In this invention, the dry basis refers to calcination at 550°C for 3 hours.
[0050] In this invention, the type of adhesive solvent is not particularly limited, and it can be any type of adhesive solvent commonly used in the art. Preferably, the adhesive solvent is an inorganic acid, and more preferably, the adhesive solvent is nitric acid.
[0051] The present invention does not have any particular limitation on the way the Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, binder, extrusion aid, and adhesive are added; they can be added separately or together.
[0052] According to a preferred embodiment of the present invention, the Beta / ZSM-12 symbiotic molecular sieve titanium dioxide, binder and optional extrusion aid are first mixed evenly, and then an aqueous solution containing adhesive solvent is added.
[0053] According to the present invention, preferably, the amount of the adhesive solvent is 2-8% of the binder weight on a dry basis. There is no particular limitation on the amount of the aqueous solution containing the adhesive solvent, and those skilled in the art can make adaptive adjustments according to the molding situation. Preferably, the amount of water in the aqueous solution containing the adhesive solvent is 20-60% of the total weight of the Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and binder on a dry basis.
[0054] The present invention does not specifically limit the mixing conditions described in step (1), and can select them appropriately according to the specific circumstances, as long as the purpose of uniform mixing can be achieved.
[0055] The present invention does not particularly limit the molding process described in step (2), and it can be carried out according to conventional molding methods in the art. For example, it can be, but is not limited to, extrusion molding, spray molding, or compression molding. Extrusion molding is preferred in the present invention, and the specific method is well known to those skilled in the art, and will not be described in detail here.
[0056] According to a specific embodiment of the present invention, the mixture obtained in step (1) is first kneaded to obtain a dough-like shape, and then extruded into a cylindrical strip.
[0057] The present invention does not particularly limit the drying conditions, which can be appropriately selected according to specific circumstances, as long as the drying purpose is achieved. Preferably, the drying conditions include: a temperature of 60-150℃ and a time of 3-12 hours.
[0058] The present invention does not particularly limit the calcination conditions, and can be carried out with reference to conventional methods in the art. The calcination is generally carried out in an air atmosphere, which includes a flowing atmosphere and may also include a stationary atmosphere. According to the present invention, preferably, the calcination conditions include: a temperature of 450-650℃, preferably 500-600℃; and a time of 2-10 hours, preferably 3-8 hours.
[0059] The third aspect of this invention provides the application of the alkyl transfer catalyst described in the first aspect in the liquid-phase alkyl transfer reaction of aromatics.
[0060] A fourth aspect of the present invention provides a method for liquid-phase alkyl transfer of aromatics, the method comprising: contacting a mixture containing toluene and C9+ aromatics with a catalyst under liquid-phase reaction conditions in the presence of hydrogen, wherein the catalyst is selected from the alkyl transfer catalyst described in the first aspect.
[0061] According to the present invention, preferably, the liquid-phase reaction conditions include: a temperature of 200-350℃, more preferably 250-300℃; a pressure of 2-5 MPa, more preferably 3-4 MPa; and a mass hourly space velocity of 0.5-2.5 h⁻¹. -1 Preferably 1-2 hours -1 .
[0062] The phrase "in the presence of hydrogen" as used in this invention is a conventional choice in the art, and various hydrogen-containing gases can be used to implement this invention, as long as the amount of hydrogen in the hydrogen-containing gas is sufficient to meet the conditions for the liquid-phase reaction of the mixture of toluene and C9+ aromatics. This invention does not have specific requirements in this regard and will not be described in detail here.
[0063] In this invention, the content of toluene and C9+ aromatics in the mixture containing toluene and C9+ aromatics has a wide range, and those skilled in the art can make adaptive adjustments according to the liquid-phase reaction. Preferably, the weight content of toluene and the weight content of C9+ aromatics in the mixture are 30-70%.
[0064] This invention allows for a wide range of C9+ aromatic hydrocarbons, as long as they can be mixed with toluene and react in the liquid phase to produce xylene. The C9+ aromatic hydrocarbons are selected from at least one of aromatic hydrocarbons having 9 or more carbon atoms.
[0065] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this invention are based on weight, unless being based on weight would not be in accordance with the common understanding of those skilled in the art.
[0066] According to a particularly preferred embodiment of the present invention, a method for preparing an alkyl transfer catalyst includes the following steps:
[0067] (1) In the presence of a solvent, the Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, binder and optional extrusion aid and adhesive solvent are mixed;
[0068] (2) The mixture obtained in step (1) is shaped, and then dried and calcined;
[0069] Based on the total amount of catalyst, the weight percentage of the Beta / ZSM-12 symbiotic molecular sieve is 74-85%; the weight percentage of titanium dioxide is 3-6%; and the weight percentage of the binder is 10-20%.
[0070] In the Beta / ZSM-12 symbiotic molecular sieve, the symbiotic ratio of Beta molecular sieve and ZSM-12 molecular sieve is 0.5-2:1.
[0071] The present invention will now be described in detail through examples and comparative examples. In the following examples and comparative examples,
[0072] The definition of aromatic hydrocarbon conversion rate is as follows:
[0073]
[0074] The selectivity of xylene is defined as follows:
[0075]
[0076] The content of aromatic hydrocarbons was determined by gas chromatography. The testing instrument was an Agilent Technologies 7890A GCSystem.
[0077] The test methods for the average grain size and silicon-aluminum molar ratio of Beta / ZSM-12 symbiotic molecular sieve are described in the aforementioned specification and will not be repeated here.
[0078] Unless otherwise specified, all reagents and materials used are commercially available, and the room temperature is 25°C.
[0079] Example 1 of Beta / ZSM-12 symbiotic molecular sieve preparation
[0080] The molar ratio of NaOH, tetraethylammonium hydroxide, silica gel, boehmite, and deionized water was calculated as: SiO2 / Al2O3 = 15:1, TEA + / SiO2=0.2:1, OH - The mixture of SiO2 (0.4:1) and H2O (20:1) was stirred at 50°C and aged for 3 hours. The mixture was then placed in a sealed container and crystallized at 160°C under autogenous pressure for 72 hours. After cooling, the crystallized product was removed, filtered, exchanged, washed with water, dried, and calcined at 550°C in air for 4 hours to obtain a Beta / ZSM-12 symbiotic molecular sieve with a SiO2 / Al2O3 molar ratio of 10.
[0081] Examples of Beta / ZSM-12 symbiotic molecular sieve preparation 2-9
[0082] Beta / ZSM-12 symbiotic molecular sieves were prepared according to the method of Preparation Example 1. The amount of each component added and the reaction conditions were changed so that the prepared Beta / ZSM-12 symbiotic molecular sieves met the conditions for preparing alkyl transfer catalysts. The SiO2 / Al2O3 molar ratio, average grain size and symbiotic ratio of Beta / ZSM-12 symbiotic molecular sieves are detailed in Table 1.
[0083] Example 1
[0084] 77g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 2:1) prepared in Example 1 (dry basis), 8g of TiO2 powder (dry basis), 15g of alumina (dry basis), and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst A was obtained, as detailed in Table 1.
[0085] Example 2
[0086] 83g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 2:1), 2g of TiO2 powder, 15g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst B was obtained, as detailed in Table 1.
[0087] Example 3
[0088] 80g of the Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 2:1), 5g of TiO2 powder, 15g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst C was obtained, as detailed in Table 1.
[0089] Example 4
[0090] 80g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 4:1), 5g of TiO2 powder, 15g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst D was obtained, as detailed in Table 1.
[0091] Example 5
[0092] 80g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 0.5:1), 5g of TiO2 powder, 15g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst E was obtained, as detailed in Table 1.
[0093] Example 6
[0094] 80g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 0.25:1), 5g of TiO2 powder, 15g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst F was obtained, as detailed in Table 1.
[0095] Example 7
[0096] 80g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 20, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 2:1), 5g of TiO2 powder, 15g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst G was obtained, as detailed in Table 1.
[0097] Example 8
[0098] 80g of the Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 150nm, Beta to ZSM-12 symbiotic ratio of 2:1), 5g of TiO2 powder, 15g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst H was obtained, as detailed in Table 1.
[0099] Example 9
[0100] 74g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 15, average grain size of 150nm, Beta to ZSM-12 symbiotic ratio of 1:1), 6g of TiO2 powder, 20g of silica sol, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of aqueous solution was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. After drying at 120℃ for 6h and calcining in air at 550℃ for 4h, catalyst I was obtained, as detailed in Table 1.
[0101] Example 10
[0102] The catalyst was prepared using the same method as in Example 3, except that the Beta / ZSM-12 symbiotic molecular sieve of Preparation Example 8 (SiO2 / Al2O3 molar ratio of 30, average grain size of 300 nm, and Beta to ZSM-12 symbiotic ratio of 2:1) was used to replace the symbiotic molecular sieve of Preparation Example 1 with an equal mass, and catalyst J was obtained, as detailed in Table 1.
[0103] Example 11
[0104] The catalyst was prepared using the same method as in Example 3, except that the content of Beta / ZSM-12 symbiotic molecular sieve was changed to 70%, and catalyst K was obtained, as detailed in Table 1.
[0105] Example 12
[0106] The catalyst was prepared using the same method as in Example 3, except that the Beta / ZSM-12 symbiotic molecular sieve of Preparation Example 9 (SiO2 / Al2O3 molar ratio of 10, average grain size of 500 nm, and Beta to ZSM-12 symbiotic ratio of 2:1) was used to replace the symbiotic molecular sieve of Preparation Example 1 with an equal mass, and catalyst L was obtained, as detailed in Table 1.
[0107] Comparative Example 1
[0108] 51.3g of Beta molecular sieve (dry basis) and 25.7g of ZSM-12 molecular sieve (dry basis, SiO2 / Al2O3 molar ratio of the two molecular sieves is 10-12, average grain size is 300nm), 8g of TiO2 powder (dry basis), 15g of alumina (dry basis), and 2.5g of guar gum powder (dry basis) were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. The catalyst was obtained after drying at 120℃ for 6h and calcining in air at 550℃ for 4h. See Table 1 for details.
[0109] Comparative Example 2
[0110] 83.7g of Beta / ZSM-12 symbiotic molecular sieve (SiO2 / Al2O3 molar ratio of 10, average grain size of 300nm, Beta to ZSM-12 symbiotic ratio of 2:1), 16.3g of alumina, and 2.5g of guar gum powder were mixed evenly in a kneader. 45g of an aqueous solution containing 1g of nitric acid was slowly added to the kneader and kneaded for 30 minutes to obtain a dough-like consistency. The dough was then extruded through a mold into cylindrical strips with a diameter of 1.7mm and a length of 2mm. The catalyst was obtained after drying at 120℃ for 6h and calcining in air at 550℃ for 4h. See Table 1 for details.
[0111] Comparative Example 3
[0112] The catalyst was prepared according to the method of Example 3, except that titanium dioxide was replaced with the same mass of zinc oxide, as detailed in Table 1.
[0113] Table 1
[0114]
[0115] Test case
[0116] The catalysts prepared in the examples and comparative examples were respectively loaded into fixed-bed reactors and subjected to temperature of 280°C, pressure of 3.5 MPa, and mass hourly space velocity of 1.5 h⁻¹. -1 The liquid-phase alkyl transfer reaction was carried out under a hydrogen atmosphere. The composition of the raw materials is shown in Table 2, and the reaction results are shown in Table 3.
[0117] Table 2
[0118] Weight content, % 50 45 5
[0119] Table 3
[0120] A 49.2 83.3 B 51.0 81.0 C 50.6 85.2 D 48.3 82.2 E 50.5 83.6 F 48.5 83.1 G 49.1 84.8 H 51.8 85.3 I 48.0 84.6 J 47.9 80.5 K 47.2 82.3 L 49.0 84.2 Comparative Example 1 30.6 55.9 Comparative Example 2 35.1 63.3 Comparative Example 3 34.4 77.3
[0121] The catalysts prepared in the examples and comparative examples were respectively loaded into fixed-bed reactors and subjected to temperature of 295°C, pressure of 4.0 MPa, and mass hourly space velocity of 1.0 h⁻¹.-1 The liquid-phase alkyl transfer reaction was carried out under a hydrogen atmosphere. The composition of the raw materials is shown in Table 2, and the reaction results are listed in Table 4.
[0122] Table 4
[0123]
[0124]
[0125] As can be seen from the results in Tables 3 and 4, the alkyl transfer catalyst provided by this invention, in combination with Beta / ZSM-12 symbiotic molecular sieve and TiO2, exhibits both higher aromatic hydrocarbon conversion and higher xylene selectivity under liquid-phase reaction conditions. It can be used in the industrial production of para-xylene to achieve the goal of increasing xylene production.
[0126] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for liquid-phase alkyl transfer of aromatic hydrocarbons, characterized in that, The method includes: in the presence of hydrogen, under liquid-phase reaction conditions, contacting a mixture containing toluene and C9+ aromatics with a catalyst comprising a Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, and a binder. Based on the total amount of catalyst, the weight percentage of the Beta / ZSM-12 symbiotic molecular sieve is 74-85%; the weight percentage of titanium dioxide is 3-6%; and the weight percentage of the binder is 10-20%. In the Beta / ZSM-12 symbiotic molecular sieve, the symbiotic ratio of Beta molecular sieve and ZSM-12 molecular sieve is 0.5-2:1; The average grain size of the Beta / ZSM-12 symbiotic molecular sieve is 100-300 nm.
2. The method according to claim 1, wherein, The SiO2 / Al2O3 molar ratio of the Beta / ZSM-12 symbiotic molecular sieve is 10-40.
3. The method according to claim 2, wherein, The SiO2 / Al2O3 molar ratio of the Beta / ZSM-12 symbiotic molecular sieve is 10-20.
4. The method according to claim 1, wherein, The binder is silicon dioxide and / or aluminum oxide.
5. The method according to any one of claims 1-4, wherein, The method for preparing the catalyst includes the following steps: (1) In the presence of a solvent, the Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide, binder, and optionally extrusion aid and adhesive solvent are mixed; (2) The mixture obtained in step (1) is shaped, and then dried and roasted.
6. The method according to claim 5, wherein, The extrusion aid is selected from at least one of guar gum powder, methylcellulose, and dextrin.
7. The method according to claim 5, wherein, The extrusion aid is hydroxypropyl methylcellulose.
8. The method according to claim 5, wherein, The amount of the extrusion aid is 1-5% of the total weight of Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide and binder on a dry basis.
9. The method according to claim 8, wherein, The amount of the extrusion aid is 1-3% of the total weight of Beta / ZSM-12 symbiotic molecular sieve, titanium dioxide and binder on a dry basis.
10. The method according to claim 5, wherein, The adhesive solvent is nitric acid.
11. The method according to claim 5, wherein, The amount of the adhesive solvent used is 2-8% of the dry weight of the adhesive.
12. The method according to claim 5, wherein, The drying conditions include: a temperature of 60-150℃ and a time of 3-12 hours; And / or, the calcination conditions include: a temperature of 450-650℃; and a time of 2-10h.
13. The method according to claim 12, wherein, The roasting conditions include: a temperature of 500-600℃ and a time of 3-8 hours.
14. The method according to claim 1, wherein, The liquid-phase reaction conditions include: a temperature of 200-350℃; a pressure of 2-5 MPa; and a mass hourly space velocity of 0.5-2.5 h⁻¹. -1 .
15. The method according to claim 14, wherein, The liquid-phase reaction conditions include: temperature of 250-300℃; pressure of 3-4 MPa; and mass hourly space velocity of 1-2 h⁻¹. -1 .
Citation Information
Patent Citations
Liquid phase transalkylation process
CN108779047A
Transalkylation of heavy aromatic hydrocarbons
CN109790084A
Disproportionation and transalkylation of heavy aromatic hydrocarbons
CN109803944A
Toluene disproportionation and transalkylation catalyst and preparation method thereof
CN101898153A
Method for producing xylene
CN115974641A
